CELIEâS CHARACTERISTIC IN ALICE WALKERâS THE COLOR PURPLE - Scientia, Sutriani (Humaniora Scientia, 2015)
This Â studyÂ  is Â related Â to Â the Â characteristics Â and Â character Â development Â of Â the Â main character in Alice Walkerâs The Color Purple, Celie. There are two objectives of the study namely, (1) to find out Celieâs characteristics, (2) to explain Ceieâscharacter development in the novel. It is a descriptive research with the novel The Color Purple as the main source of data. The data were collected through library study and internet browsing. This research made use of the theories of character, characterization, psychology, personality, and personality development. Moreover, sociological and psychological approaches were applied to analyze the data. The data analysis shows as follows: (1) Celieâs characteristics include weakness, patience, obedience, and lovability, (2) Celieâs character development causes Celie to be a cheerful, brave, and hard worker woman. Â  Key Words : Characteristic, Character Development, Characterization Â